Synthesis, structural studies and biological properties of some phosphono-perfluorophenylalanine derivatives formed by SNAr reactions12. Issue 42 (5th August 2019) - Kwiczak-Yiğitbaşı, Joanna; Pirat, Jean-Luc; Virieux, David; Volle, Jean-Noël; Janiak, Agnieszka; Hoffmann, Marcin; Mrzygłód, Jakub; Wawrzyniak, Dariusz; Barciszewski, Jan; Pluskota-Karwatka, Donata
Abstract : Several novel phosphono-perfluorophenylalanine derivatives, as mimetics of phenylalanine, were synthesized by subjecting diethyl (2-(perfluorophenyl)-1-(phenylamino)ethyl)-phosphonate to SN Ar reactions with thiols, amines and phenols. Abstract : Several novel phosphono-perfluorophenylalanine derivatives, as mimetics of phenylalanine, were synthesized by subjecting diethyl (2-(perfluorophenyl)-1-(phenylamino)ethyl)-phosphonate to SN Ar reactions with different types of nucleophiles such as thiols, amines and phenols. The structure of the products was confirmed using spectroscopic and spectrometric techniques. For two compounds X-ray single crystal diffraction analysis and DFT investigations were performed providing information in regard to the preferable conformation, hydrogen bonds and other interactions. The antiproliferative potency of some of the new phosphono-perfluorophenylalanine derivatives obtained as well as representatives of previously synthesized perfluorophenyl phosphonate analogues of phenylalanine was studied on selected glioma cell lines. Preliminary evaluation of the compounds drug likeness was examined with respect to Lipinski's and Veber's rules, and showed that they meet the criteria perfectly. MTT (3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2 H -tetrazolium bromide) assay results demonstrated that the compounds exhibit moderate activity against the glioblastoma multiforme cell lines (T98G and U-118 MG). Moreover most of the studied SN Ar reaction products displayed significantly higher inhibitory activity against both cancer cell lines than the parent diethyl (2-(perfluorophenyl)-1-(phenylamino)ethyl)phosphonate.